Piosenka przypomni ci ... (Gdańsk : [wydawca nieznany], 1960)
Afisz informujący o występach w sopockim kinie Bałtyk 26.03.1960 r.
Keywords: Kina -- Polska -- Sopot -- 1945-1970 -- druki ulotne; Życie artystyczne -- Polska -- Sopot -- 1945-1970 -- druki ulotne